PENERAPAN KOMUNIKASI MEMANFAATKAN WHATSAPP GATEWAY ANTARA ADMIN DAN CALON SISWA BARU PADA MADRASAH ALIYAH ISY KARIMA - Azis, Abdul; Riyanto, Agus; Evi Yuliana, Margaretha (Penerbit Lafadz Jaya, 2023)
This article discusses the application of WhatsApp gateway in communication between administrators and prospective students at Madrasah Aliyah Isy Karima. A WhatsApp gateway is the use of an API or software solution to integrate WhatsApp messaging capabilities into an application, system or website. This article reviews the potential of implementing a WhatsApp gateway to improve the effectiveness and efficiency of communication. The bibliography includes references to UltraMsg as an API provider and the GitHub repository for other options. The discussion includes the benefits of using the WhatsApp Gateway API for automated messages, auto-replies, and message tracking. It is important to adhere to WhatsApp policies and guidelines. Overall, the implementation of WhatsApp gateway can improve communication with prospective students and strengthen the admission process at Madrasah Aliyah Isy Karima.